Spontaneous bile duct perforation causing biliary peritonitis in chronic pancreatitis - Mukesh Kumar; Sanjit Prasad; Vivek Kumar Roy; Lavudya Mahesh; Krishna Gopal (Wolters Kluwer -Medknow Publications, 2023)
Spontaneous perforation of the extrahepatic biliary system is a rare presentation of chronic pancreatitis. Very few cases of bile duct perforation have been reported in adults. It is rarely correctly diagnosed preoperatively in an emergency. A 25-year-old male presented at the surgical emergency with a long history of abdominal pain and repeated episodes of vomiting, after 4 days of duration, he came with pain abdomen, and distension with evidence of generalized peritonitis. The diagnosis made was perforative peritonitis for which he underwent an exploratory laparotomy with cholecystectomy. A single perforation was presented on the anterolateral surface of the supraduodenal part of the common bile duct (CBD) which was repaired with the help of T-tube. On the 10th post-operative day, T-tube cholangiogram shows two radio-opaque dense shadows in the main pancreatic duct which shows chronic pancreatitis and lower CBD stricture. Spontaneous perforation of the extrahepatic bile duct is a rare but important presentation of chronic pancreatitis in adults causing biliary peritonitis. Therefore, awareness of the clinical presentation, expert ultrasound examination, and surgery are important aspects of the management.